The effectiveness of oral presentation assessment in a Finance subject: An empirical examination - Bhati, Shyam (Journal of University Teaching and Learning Practice, 2012)
The purpose of this paper is to study the effectiveness of oral presentation as an assessment tool in a Finance subject. Assessment data collected from a postgraduate Finance subject in an Australian university over a period of five years from 2005 to 2009 was analysed statistically to determine the relation between students’ performance in oral presentation and other forms of assessments. The sample consists of assessment records of 412 students and 98 group presentations. From the study of correlations between oral presentations and other assessments, it is concluded that students perform better in written assessments compared to oral assessment. The study of effect of gender on students’ performance leads to the conclusion that female students perform better than male students in all forms of assessments except oral presentations where male students perform better although difference between males and females in oral presentation is not very large. The study of students’ performance based on their nationality leads to the conclusion that domestic students perform better than international students in all forms of assessments. Based on the study of student’ performance in oral presentation, it is found that students did well in the development of content of presentations, quality of their analysis, group coordination and organisation of presentation. There is however a general tendency to treat group work as a sum of parts instead of treating the group work as a single task. This study is limited by the fact that effectiveness of oral presentation is studied in only one Finance subject. This study makes an original contribution to the literature as the effectiveness of oral assessment in Finance subject is being studied for the first time. The conclusions arrived in this paper have many implications for policies and practice of learning and teaching in Finance.